(untitled) (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2023)
Immunization is essential for preventing infectious diseases and lowering death and disability, especially in young children. Low vaccination coverage rates do, however, continue to exist in many areas, underscoring the significance of knowing what causes less-than-ideal uptake. A total of 302 nursing mothers were recruited for this study. A structured semi- questionnaire was used to assess the respondents’ knowledge of routine immunization, Attitudes towards immunization and factors influencing uptake were also explored. The findings revealed that 93.0% of the nursing mothers had heard about immunization, with the majority acquiring information from friends and family (69.9%). Knowledge regarding specific vaccines and their timing varied, with 45.0% correctly identifying BCG as the first immunization at birth. While 51.0% believed that a child receives the measles vaccine at 9 months, other responses varied. Compliance with the infant immunization schedule was suboptimal, as 46.0% of the respondents had poor compliance. Significant associations were found between sociodemographic factors (age, marital status, education, religion, occupation, husband’s education, and family income) and both knowledge levels and compliance The findings suggest the need for targeted interventions to improve knowledge and awareness among nursing mothers regarding routine immunization. Efforts should focus on addressing barriers such as long distances to immunization Centre’s and the cost. Additionally, involving husbands in promoting immunization can enhance acceptance and uptake. Policymakers and healthcare providers should collaborate to develop strategies that enhance the accessibility, affordability, and acceptability of immunization services.